Probable sarcopenia is associated with cognitive impairment among community-dwelling older adults: results from the FIBRA study - Gabriela Cabett Cipolli; Ivan Aprahamian; Flávia Silva Arbex Borim; Deusivania Vieira Silva Falcão; Meire Cachioni; Ruth Calderia de Melo; Samila Sathler Tavares Batistoni; Anita Liberaleso Neri; Mônica Sanches Yassuda (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The link between sarcopenia and cognitive impairment has not yet been thoroughly evaluated, especially among older adults. Objective: To evaluate the relationship between probable sarcopenia and cognitive impairment among community-dwelling older adults in two Brazilian cities. Methods: Probable sarcopenia was assessed using the EWGSOP2 (2018) criteria. Thus, participants were classified as probably having sarcopenia if they had SARC-F (Strength, Assistance in walking, Rise from a chair, Climb stairs and Falls) ≥4 points and low grip strength. Cognitive function was evaluated through the Mini-Mental State Examination (MMSE), verbal fluency (VF) and clock drawing test (CDT). Results: In a sample of 529 older adults (mean age 80.8±4.9 years; mean education 4.2±3.67 years; 70.1% women), 27.3% of the participants had SARC-F≥4, 38.3% had low grip strength and 13.6% were classified as probable sarcopenia cases. After adjusting for possible confounders (age, sex, education, depression, diabetes, hypertension, leisure-time physical activity and obesity), probable sarcopenia was found to be associated with impairment in the MMSE (OR 2.52; 95%CI 1.42‒4.47; p=0.002) and in VF (OR 2.17; 95%CI 1.17‒4.01; p=0.014). Low grip strength was found to be associated with impairment in the MMSE (OR 1.83; 95%CI 1.18‒2.82; p=0.006) and in the CDT (OR 1.79; 95%CI 1.18‒2.73; p=0.006). SARC-F scores were found to be associated with impairment in the MMSE (OR 1.90; 95%CI 1.18‒3.06; p=0.008). Conclusion: The results suggested that probable sarcopenia and its components present a significant association with cognitive deficits among community-dwelling older adults. Future longitudinal studies will further explore the causal relationship.